2012
DOI: 10.1016/j.jchemneu.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

PlexinA4 distribution in the adult rat spinal cord and dorsal root ganglia

Abstract: PlexinsA1–A4 participate in class 3 semaphorin signaling as co-receptors to neuropilin 1 and 2, PlexinA4 being the latest member of the PlexinA subfamily to be identified. Little is known about the cellular distribution of PlexinA4 in the spinal cord and dorsal root ganglion (DRG). Here, immunohistochemical studies using antibodies to PlexinA4 revealed immunolabeling in neurons in both dorsal and, to a greater extent, ventral horns of the spinal cord. Ventral horn PlexinA4 positive neurons exhibited morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…In two previous studies we described the expression of PlexinA4 in the adult brain and spinal cord suggesting a role beyond the early stages of development (Gutekunst, Stewart et al 2010; Gutekunst, Stewart et al 2012). Here we provide the first description of PlexinA4 distribution in the adult rat cranial nerves.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In two previous studies we described the expression of PlexinA4 in the adult brain and spinal cord suggesting a role beyond the early stages of development (Gutekunst, Stewart et al 2010; Gutekunst, Stewart et al 2012). Here we provide the first description of PlexinA4 distribution in the adult rat cranial nerves.…”
Section: Discussionmentioning
confidence: 91%
“…The specificity of the antibodies used in this study has been extensively described in our previous studies (Gutekunst, Stewart et al 2010; Gutekunst, Stewart et al 2012). PlexinA4 is detected using a rabbit polyclonal antibody that was raised against a synthetic 16 amino acid peptide derived from within residues 500–600 of mouse PlexinA4, identical to that of rat PlexinA4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7). High levels of Plexin A4 have been previously demonstrated in the lumbosacral region (Mauti et al, 2006) and in rat sciatic nerve (L4–L6) for DRG (Gutekunst et al, 2012). Plexin A2 has also been identified as a potential Sema6A suppressing receptor (Suto et al, 2007) and expression has been reported to be more prominent rostrally in DRG, with lumbosacral DRG showing only a subset of cells expressing the receptor (Mauti et al, 2006).…”
Section: Discussionmentioning
confidence: 93%